Neuropsychological Rehabilitation of Childhood Brain Injury
XVI, 297 p.
Keywords: While brain injury can be a potentially devastating childhood medical condition this book explores the developing field of neuropsychology to suggest it is not inevitable. It draws together contributions from leading international clinicians and researchers to provide an authoritative guide to help children with brain injury using neuropsychology.